Trends and predictors of HIV positivity and time since last test at voluntary counselling and testing encounters among adults in Kilifi, Kenya, 2006-2017 - Mugo, PM; Agutu, CA; Wahome, E; Juma, M; Nzioka, J; Mohamed, K; Mumba, T; Shally, M; Fauz, I; Omar, A; Rinke de Wit, TF; van der Elst, EM; et al. (F1000Research, 2019)
Background: Little is known about HIV retesting uptake among key populations (KP) and general populations (GP) in Kenya. We assessed trends and predictors of first-time testing (FTT), late retesting (previous test more than one year ago for GP or three months for KP), and test positivity at three voluntary counselling and testing (VCT) centres in coastal Kenya.